The Legal Status of Religious Groups in Argentina: Toward a Multi-Confessional System - Arlettaz, Fernando (Journal of law, religion and state, 2019)
The Argentinian Constitution of 1853 established a religious policy based on two main principles: freedom of religion and the privileged status of the Catholic Church. In 1966, an agreement with the Catholic Church eliminated the power of the government to interfere in ecclesiastical matters, but maintained the privileged status of Catholicism. Today, the religious configuration of Argentinian society differs greatly from that of the 19th century. Amidst increasing religious diversity, some legal changes point to the transformation of the Argentinian regime from a nearly confessional state into a multi-confessional, yet not an egalitarian one.